PEMBELAJARAN AQIDAH AKHLAK MENGUNAKAN METODE BERNYANYI UNTUK MEMBANTU DAYA INGAT SISWA KELAS III DI MADRASAH IBTIDAIYAH NEGERI (MIN) 1 ACEH TENGAH - Suwarno Suwarno; Akrima Dini; Maulida Yani; Sahria Nurul Yana; Susilawati Susilawati (TA'LIM : Jurnal Studi Pendidikan Islam, 2022)
Learning is a process of interaction between teachers and students to achieve learning objectives. In performing these learning objectives, the teacher will strive optimally by carrying out various strategies and learning methods. This study focuses on using the singing method to help students' memory. This study aimed to discover the technique of singing in growing students' memory in the subjects of aqidah morality at MIN 1 Aceh Tengah. The research method used is qualitative. Sources of data in the form of primary data and secondary data. Data collection techniques using observation and interviews. Meanwhile, data analysis uses analysis according to Miles and Huberman, including data reduction, display, and verification. The results showed that the singing method in learning aqidah akhlaq in class III MIN 1 Aceh Tengah could help students' memory.